Cable railway mechatronic drive dynamics simulation - Samsonov A.V. (Научно-технический вестник Брянского государственного университета)
Dynamic analysis of one of the designs of mechatronic drive with flexible traction body innovative transport system "Kanatnoe metro" is under consideration in this article. The dynamic model consists of distributed elastic elements con-nected by elastic-dissipative links.